新加坡华人平翘舌音的识别和产出 = Chinese Singaporeans' phonological discrimination and articulation of blade alveolars and retroflexes - 洪玮嬣 Ang, Shermaine Wei Ning (Nanyang Technological University, 2023)
这项研究旨在调查新加坡华人平翘舌音[t͡s]、[t͡sʰ]、[s] 和[ʈ͡ʂ]、[ʈ͡ʂʰ]、[ʂ] 的辨别能力以及发音方式。本次研究所设的听辨实验要求受试者区分两个听起来相似的词，两者的差别在于一个是平舌音，另一个是翘舌音。通过此实验，受试者平翘舌音的辨别能力得到了检验。研究结果显示受试者更擅长辨别翘舌音。之后,本次研究通过使用单因素ANOVA 和 t-检验探讨社会因素对受试者平翘舌音的辨别能力是否有显著性的影响。结果显示，年龄、性别和教育水平对此有显著的影响。此外，这项研究结合了经典拉波夫社会语言学的测试法例如,(1)按语音相似度排列的单词表，(2)随意排列的单词表和(3)阅读短文,以探讨新加坡华人平翘舌音的发音情况。ANOVA 和 t-检验的结果表明，年龄、性别、教育水平和方言的使用频率对受试者平翘舌发音有显著的影响。其次，本文通过结合前两项研究实验的结果，探讨辨别能力与发音方式之间的相关性。最后，本文讨论了所发现语言现象背后的可能原因，以及对新加坡汉语拼音教学的启示。This study investigates the phonological discrimination skills and articulation of Chinese Singaporeans with respect to blade alveolars [t͡s]、[t͡sʰ]、[s] and retroflexes [ʈ͡ʂ]、[ʈ͡ʂʰ]、[ʂ] in Mandarin Chinese. Participants performed a series of tasks to distinguish between two similar-sounding words, and their discrimination abilities were examined. Results showed that participants were better at identifying retroflexes than blade alveolars. ANOVA and t-tests were used to assess the significance of social factors on participants' discrimination abilities, with age, gender and education level found to have a significant effect. The study also used classic Labovian methods such as minimal pair lists, word lists and reading passages to investigate the impact of social factors on pronunciation. Results revealed that age, gender, education level, and frequency of usage of Chinese dialects significantly influenced pronunciation. Additionally, the study examined the correlation between phonological discrimination skills and articulation. The final section discusses the reasons for the observed phenomena as well as pedagogical implications of the above findings. It is in hope that this research will provide a deeper insight of the usage and understanding of blade alveolars and retroflexes in Singapore, building upon previous studies.